The mechanism of an amorphous-crystalline fat formation in the submicrostructure of butter - Gulyy, Ivan; Rashevska, Tamara; Pryadko, Nikolai; Nischenko, Michael; Lihtorovich, Stanislav (My University, 2001)
The processes of the butter structure formation have been studied by the electron microscopy method which showed that it contains destroyed and partially impaired fat globules. Процеси формування структури вершкового масла були вивчені методом електронної мікроскопії, яка показала, що структура містить зруйновані і частково зруйновані жирові кульки.
Keywords: butter; вершкове масло; жирова кулька; кафедра технології молока і молочних продуктів